Dynamics of Aggregate Consumption in Niger - Sow, Safiatou Latifa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This study attempts to analyse the relationship between consumption expenditure and income from 1960 to 2018 in Niger. We used the Dual Adjustment approach which models the dual co-movements of the variables, as an alternative to the traditional cointegration analysis that implicitly enforces a singular adjustment between the variables. Our results provide evidence on the existence of common Hodrick Prescott trend for income and consumption in Niger. The results also show a significant relationship between the transitory components of our variables. Overall, our results indicate that Dynamic Keynesian Consumption Function is valid for Niger. Our results also show that an increase in income leads to a decrease in the Average Propensity to Consume (APC) and hence increase in the Average Propensity to Save (APS). Furthermore, our findings suggest that an increase in public expenditure can help to stimulate the economic growth of Niger. Keywords: Household Consumption Expenditure, Income, Cointegration, Dual Adjustment

ÖZ: Bu çalışma, Nijer'de 1960-2018 dönemi için tüketim harcamaları ile gelir arasındaki ilişkiyi analiz etmeyi amaçlamaktadır. Değişkenlerin ortak ikili hareketlerini modelleyen İkili Uyarlanma yaklaşımını, değişkenler arasında örtük olarak tekil bir uyarlamayı içeren geleneksel eşbütünleşme analizine bir alternatif olarak kullandık. Sonuçlarımız Nijer'de gelir ve tüketime yönelik ortak Hodrick Prescott eğiliminin varlığına dair ampirik bulgular sağlıyor. Sonuçlar ayrıca değişkenlerimizin geçici bileşenleri arasında önemli bir ilişki olduğunu göstermektedir. Genel olarak, sonuçlarımız Dinamik Keynesyen Tüketim Fonksiyonunun Nijer için geçerli olduğunu göstermektedir. Sonuçlarımız ayrıca, gelirdeki bir artışın Ortalama Tüketim Eğiliminde (APC) bir azalmaya yol açtığını ve dolayısıyla Ortalama Tasarruf Eğilimi'ni (APS) artırdığını göstermektedir. Ayrıca, bulgularımız kamu harcamalarındaki bir artışın Nijer'in ekonomik büyümesini canlandırabileceğini göstermektedir. Anahtar Kelimeler: Hanehalkı Tüketim Harcamaları, Gelir, Eşbütünleşme, İkili Uyarlanma
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2020. Supervisor: Prof. Dr. Mustafa İsmihan.
Keywords: Economics; Consumption (Economics)--Nigeria; Household Consumption Expenditure; Income; Cointegration; Dual Adjustment